Efficacy and safety of arthroscopic surgery combined with hyaluronic acid for meniscal injuries: A systematic review and meta-analysis of randomized controlled studies. (1st March 2023) - Dong, Zhiqiang; Huang, Lingan; Wu, Gaige; Li, Pengcui; Wei, Xiaochun
Objective: The efficacy and safety of arthroscopic surgery combined with hyaluronic acid in the treatment of meniscal injuries were evaluated by Meta-analysis to provide an evidence-based basis for the selection of clinical treatment options. Methods: PubMed, Cochrane Library, EMBASE, Scopus, Web of Science English databases, and Chinese databases of China National Knowledge Infrastructure, WAN FANG, VIP, and China SinoMed had been searched up to June 2021. Quality evaluation was performed concerning the Cochrane Systematic Evaluation Tool. The obtained data were analyzed using the statistical software Review Manager 5.3. Results: Eleven randomized controlled trials with a total of 955 patients were eventually included, 473 in the arthroscopic combined with hyaluronic acid group (combined treatment group) and 482 in the arthroscopy alone group (surgery group). The results of the study revealed that the excellent treatment [OR = 3.44, 95% CI (2.10, 5.65), p < .00, 001], the VAS score [MD = −0.99, 95% CI (−1.50, −0.48), p = .0002], the Lysholm score [MD = 9.70, 95% CI (6.41, 12.99), p < .00, 001] and the joint mobility [MD = 6.31, 95% CI (0.84, 11.78), p = .02] of the combined treatment group were significantly better than the surgery group, the difference was statistically significant. The complications rate was comparable in both groups [OR = 0.86, 95% CI (0.29, 2.53), p = .78], with no statistically significant difference. Conclusion: Arthroscopic surgery combined with hyaluronic acid for meniscal injury can improve the efficiency of treatment compared with arthroscopic surgery alone, as well as the efficacy in relieving joint pain and improving joint function and mobility, without increasing the incidence of complications. Arthroscopic surgery combined with hyaluronic acid administration has good effectiveness and safety profile. Therefore, hyaluronic acid supplementation is recommended after arthroscopic surgery when treating meniscal injuries.